INCIDÊNCIA E SEVERIDADE DE MOFO BRANCO EM SOJA CULTIVADA SOB DIFERENTES DENSIDADES POPULACIONAIS E ESPAÇAMENTOS - Beruski, Gustavo Castilho (2013)
The fungus Sclerotinia sclerotiorum (Lib.) de Bary is a necrotrophic and polyphagous pathogen with soybean crop as one of the most important hosts. However in order to occur epidemics caused by such a pathogen it is necessary that the climatic conditions, mainly air temperature and relative humidity be favorable to the occurrence and development of the disease. Face with that, the current research aimed to analyze the incidence and severity of S. sclerotiorum on soybean plants grown at Arapoti, PR, Brazil, as a function of different plant populations, between row spacing’s and microclimate. The experiment was conducted in a naturally infested area with 31 sclerotia per square meter. The soybean crop (cv. Apollo RR) was sown on October 18th, 2011. The experimental design adopted herein was a randomized block in a factorial combination with 4 row spacing’s (0.35, 0.45, 0.60, 0.75 m) and 4 plant populations (150, 200, 250; 300 thousands plants per hectare), totaling 16 treatments and 4 replications. Throughout the current study we performed 4assessments of incidence and severity. The local meteorological data were collected by electronical sensors, which were attached to a CR-1000 datalogger (Campbell Scientific Inc.) being programmed to provide readings at each 60 seconds and storing averages at each 30 minutes. In compliance with the data monitored by an automatic weather station we observed that the local climatic conditions were favorable to the incidence and development of the pathogen. Throughout the crop cycle the average air temperature was of 19.5 °C, whereas during the flowering stage of the soybean crop such a variable was of 20.2 °C. The amount of rainfall was high and well distributed over course of the crop growing season, promoting favorable environmental conditions to trigger the development of the white mold in the field.Moreover, the regime of relative humidity and leaf wetness duration lead to favorable conditions to the progress of the disease at the studied site. Among the models used for epidemiological analysis, the molecular and logistic models showed the best adjustment to the data of incidence and severity of white mold on soybean crop, respectively. Pearson correlation coefficients obtained by means of a simple linear regression study between incidence and disease severity degree and local meteorological elements showed a high accuracy for the variables such as mean and maximum temperatures, confirming that these elements had a larger influence on the progress of the disease. As to the other meteorological elements the values of R were low. Yield and weight of thousand grain data did not show significant variations as a function of incidence and severity of white mold for soybean crop grown at the site in study. However, the yield was higher at treatments with reduced spacings,whereas for thousand grain weight higher values at treatments with low population densities were found herein.